The Relationship Of Narcistic Personality Trends With Mastrubation In Adolescent Boys In Junior High School 5 Sibolga In 2021 - Lilis Novitarum; Ance Siallagan; Reni Lestari (Sean Institute, 2022)
Background : Masturbation is very common among teenagers. Masturbation is influenced by growth development factors of reproductive organs that occur in adolescents. In addition, it is also heavily influenced by external factors such as magazines, films, and others that smell pornographic. Masturbation can be done quickly, anywhere as long as there is privacy, and whenever teenagers want it. The narcissistic level will affect the process of thinking and behaving. The emergence of self-esteem makes teenagers not easily careless to take actions that can lower their self-confidence and can control their sexual behavior. Methods: This study used a correlation research research design with a cross sectional design. The sampling technique was purposive sampling technique as many as 92 3rd grade students at SMP Negeri 5 Sibolga. Results: The results showed that the tendency of male adolescent narcissistic personality was high (80.4%), masturbation in male adolescents was high (93.5%). Based on the results of the fisher exact alternative statistical test, p-value = 0.001 where (p<0.05), so Ha is accepted, it means that there is a relationship between narcissistic personality tendencies and masturbation in adolescent boys at SMP Negeri 5 Sibolga in 2021 Conclusion: This study It is hoped that the next researcher will be able to increase knowledge and insight about narcissistic personality with masturbation because the results of narcissism with high masturbation are then carried out interventions to reduce the masturbation behavior masturbation in adolescent boys is high (93.5%). Based on the results of the fisher exact alternative statistical test, p-value = 0.001 where (p<0.05), so Ha is accepted, it means that there is a relationship between narcissistic personality tendencies and masturbation in adolescent boys at SMP Negeri 5 Sibolga in 2021 Conclusion: This study It is hoped that the next researcher will be able to increase knowledge and insight about narcissistic personality with masturbation because the results of narcissism with high masturbation are then carried out interventions to reduce the masturbation behavior masturbation in adolescent boys is high (93.5%). Based on the results of the fisher exact alternative statistical test, p-value = 0.001 where (p<0.05), so Ha is accepted, it means that there is a relationship between narcissistic personality tendencies and masturbation in adolescent boys at SMP Negeri 5 Sibolga in 2021 Conclusion: This study It is hoped that the next researcher will be able to increase knowledge and insight about narcissistic personality with masturbation because the results of narcissism with high masturbation are then carried out interventions to reduce the masturbation behavior